Acute and subacute evaluation of plasma glucose with circuit strength training in young adults: Study protocol - Fernando Alves, Welyngton; Cunha, Raphael Martins da (Manual Therapy, Posturology & Rehabilitation Journal, 2024)
Background: Strength training with physical exercise improves glycemic stability during exercise and reduces the duration and severity of post-exercise hypoglycemia in individuals with type 2 diabetes. Even though the effects of exercise on health are vast in the literature, the acute and sub-acute response of plasma glycemia with circuit strength training (CST) in young individuals is very scarce. Objectives: Develop a study protocol to evaluate plasma glycemic behavior in healthy young adults before, during and after CST with active rest. Methods: This is a cross-sectional study. Participants will be selected based on certain variables of interest, informed about the study, and signing the informed consent. Participants will undergo anamnesis, anthropometric assessment collection, in order to outline the physical-functional profile, taken to the weight room, where they will spend 10 minutes in a sitting position to collect pre-protocol capillary blood, one group will carry out a session with control protocol without exercise and another, a session with an experimental protocol with CST and will have plasma glucose collected between and post-protocols. Results: This cross-sectional study protocol is expected to contribute additional information on understanding the acute and subacute effects of plasma glycemia with CST, with active rest, in young individuals.